PENDAMPINGAN MAHASISWA DALAM KEGIATAN OBSERVASI PENGENALAN LAPANGAN PRASEKOLAH DI SD NEGERI 3 LAMANGGA KOTA BAUBAU - Tarno Tarno; Muhammad Yusnan; Salsa Welyana; Siti Maryam; Mufirda Mufirda (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2022)
The purpose of this community service activity at SD Negeri 3 Lamangga is to help students become more proficient in managing Preschool Field Introduction Program activities. Students will practice direct observation of school culture, observation to develop competence, and direct observation of the learning process in class during this community service activity. Teachers, staff and supervising lecturers at SD Negeri 3 Lamangga also guide students in carrying out this observation activity so that it can be realized in further activities. The method used in this service uses a field survey method. This program involves school principals and teachers at SD Negeri 3 Lamangga. The results of this service show that students have achieved the indicators set such as observation, attitude and discipline very well with a score weight of 1075.03 with an average score of 89.59.